Analysis of Bus Accessibility Based on GIS and Big Data of Crowd -- Taking Wansheng Economic Development Zone as an example. Issue 1 (February 2021) - Xiao, Hai; Liang, Xu; Zheng, Yuan; Xia, Xinyi
Abstract: Public transportation issues are increasingly becoming a key constraint to the sustainable development of urban economic and social development. Based on crowd big data and GIS spatial analysis methods, this article analyzes the accessibility of the public transportation in Wansheng Economic and Technological Development Zone (hereinafter referred to as the development zone). A comprehensive evaluation and analysis was conducted to study the matching relationship between population density and existing public transportation stations, and to propose the optimal suggestions. The results show that the overall public transportation accessibility in the development zone is average level, and the public transportation accessibility is better in the densest crowded areas, but in the east and southeast of the development zone, crowd activities are poorly matched with the public transportation network, and residents' travel demands can't get public transportation with timely responses.